Equitable Performance Fees for Hedge Funds - LEE, David K. C. (Institutional Knowledge at Singapore Management University, 2003)
Hedge funds are collective investment vehicles fast becoming popular with high net worth individuals as well as institutional investors. Given an incentive structure that involves fees based on performance, this paper proposes a structure and "equalization" process that is both equitable and transparent to investors. The structure involves the use of multi-portfolios giving any fund a structure similar to that of a partnership organization. The "equalization" process is demonstrated using stylized examples that illustrate the equalization procedures and computations. We believe that the approach improves on current methods and meets the objectives of equity and transparency, thus improving the incentive compatibility between the fund manager and investors.